2016
DOI: 10.1177/1045389x16679285
|View full text |Cite
|
Sign up to set email alerts
|

Resilient deconstructible columns for accelerated bridge construction in seismically active areas

Abstract: This article presents an unprecedented concept for resilient bridge columns comprising precast modules designed for disassembly. Resiliency is provided by superelastic shape memory alloys that minimize permanent drift and engineered cementitious composite that minimizes damage, while keeping the rest of the column elastic. The precast modules consist of prefabricated plastic hinges and prefabricated concrete-filled fiber–reinforced polymer tubes. The columns are very desirable candidates for accelerated bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…To resolve the issues inherent in superelastic Ni-Ti SMAs-e.g., low cold workability (or brittleness), low machinability, and high material cost-superelastic Cu-Al-Mn SMA rods have been developed (Kainuma et al 1996(Kainuma et al , 1998Sutou et al 2002Sutou et al , 2005Sutou et al , 2013Omori et al 2013;Kusama et al 2017). Studies have also been done on how the material can be used for improving the response of civil structures, like buildings and bridges, against earthquakes (Shrestha et al 2013;Hosseini et al 2015;Araki et al 2016;Varela and Saiidi 2017). Superelasticity is enhanced in a bamboo or columnar grained structure 1 Manager, Technology Development Dept., Special Metals Div., Furukawa Techno Material Co. Ltd., 5-1-8, Higashi-Yawata, Hiratsuka 2540016, Japan (corresponding author) (Kainuma et al 1998;Sutou et al 2002;Liu et al 2015), but the best superelasticity can be obtained in a single crystal in Cu-Al-Mn SMAs (Omori et al 2020;Kise et al 2021), which can be produced with cyclic heat treatment (Omori et al 2013;Kusama et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To resolve the issues inherent in superelastic Ni-Ti SMAs-e.g., low cold workability (or brittleness), low machinability, and high material cost-superelastic Cu-Al-Mn SMA rods have been developed (Kainuma et al 1996(Kainuma et al , 1998Sutou et al 2002Sutou et al , 2005Sutou et al , 2013Omori et al 2013;Kusama et al 2017). Studies have also been done on how the material can be used for improving the response of civil structures, like buildings and bridges, against earthquakes (Shrestha et al 2013;Hosseini et al 2015;Araki et al 2016;Varela and Saiidi 2017). Superelasticity is enhanced in a bamboo or columnar grained structure 1 Manager, Technology Development Dept., Special Metals Div., Furukawa Techno Material Co. Ltd., 5-1-8, Higashi-Yawata, Hiratsuka 2540016, Japan (corresponding author) (Kainuma et al 1998;Sutou et al 2002;Liu et al 2015), but the best superelasticity can be obtained in a single crystal in Cu-Al-Mn SMAs (Omori et al 2020;Kise et al 2021), which can be produced with cyclic heat treatment (Omori et al 2013;Kusama et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The seismic design method was validated in a shake‐table test of a two‐column bridge bent . Several other studies were conducted at the University of Nevada, Reno utilizing column cap beam pipe pins in CIP and precast test models as well as a two‐span bridge model designed for deconstruction . They demonstrated that properly designed pipe pins transfer negligible moment.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that properly designed pipe pins transfer negligible moment. Moreover, they can be designed to remain elastic during earthquake . The pipe pins in all of the aforementioned studies were at the top of the columns and were not subjected to any appreciable tension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations